Innovative Disulfide Esters of Dithiocarbamic Acid as Women‐Controlled Contraceptive Microbicides: A Bioisosterism Approach. Issue 10 (4th September 2015) - Mandalapu, Dhanaraju; Lal, Nand; Kumar, Lokesh; Kushwaha, Bhavana; Gupta, Sonal; Kumar, Lalit; Bala, Veenu; Yadav, Santosh K.; Singh, Pratiksha; Singh, Nidhi; Maikhuri, Jagdamba P.; Sankhwar, Satya N.; et al.
Abstract In an ongoing effort to discover an effective, topical, dual‐function, non‐surfactant contraceptive vaginal microbicide, a novel series of 2, 2′‐disulfanediylbis(3‐(substituted‐1‐yl)propane‐2, 1‐diyl) disubstituted‐1‐carbodithioates were designed by using a bioisosterism approach. Thirty‐three compounds were synthesized, and interestingly, most demonstrated multiple activities: they were found to be spermicidal at a minimal effective concentration of 1–0.001 %, trichomonacidal against drug‐susceptible and resistant Trichomonas strains at minimal inhibitory concentration (MIC) ranges of 10.81–377.64 and 10.81–754.14 μM, respectively, and fungicidal at MIC 7.93–86.50 μM. These compounds were also found to be non‐cytotoxic to human cervical (HeLa) epithelial cells and vaginal microflora (Lactobacilli) in vitro. The most promising compound, 2, 2′‐disulfanediylbis(3‐(pyrrolidin‐1‐yl)propane‐2, 1‐diyl)dipyrrolidine‐1‐carbodithioate (5), exhibited spermicidal activity 15‐fold higher than that of the marketed spermicide Nonoxynol‐9 (N‐9) and also demonstrated microbicidal potency. To identify common structural features required for spermicidal activity, a 3D‐QSAR analysis was carried out, as well as in vivo efficacy studies and fluorescent labeling studies to determine the biological targets of compound 5.